Clinical effects of stereotactic radiation surgery in patients with metastatic melanoma. Issue 8 (20th May 2013) - Mikoshiba, Asuka; Uhara, Hisashi; Murata, Hiroshi; Okuyama, Ryuhei
Abstract: We examined the effectiveness of stereotactic radiation surgery (SRS) in 14 patients with brain metastasis in our hospital. The age of the patients ranged 45–85 years old (mean, 65). Brain metastasis was detected by neurological symptoms in seven patients and by regular imaging examination in the remaining patients. The number of metastatic lesions in the brain before SRS ranged 1–11 (median, 2). The treatment number of SRS was 1–4 times (median, 2). Six of 14 patients had neurological symptoms before SRS. Overall survival (OS) after SRS was 1.7–21.2 months (median, 8.2). The progression‐free survival (PFS) after SRS was 0.9–10.5 months (median, 2.2). The result of univariate analysis showed that the application of two or more courses of SRS was significantly related to OS ( P  = 0.005). Single metastatic lesion ( P  = 0.051) and no extracranial lesion ( P  = 0.055) showed a slight tendency to be related to disease‐free survival (DFS). Neither lactate dehydrogenase nor neurological symptoms were significantly related to OS or DFS. Although OS and DFS after SRS were not very long, the treatment of brain metastases has the potential to prevent neurological events. Repeating SRS may be accepted as a local therapy in the multimodal approach including new molecular targeting drugs for metastatic melanoma.